2016
DOI: 10.11646/zoosymposia.11.1.15
|View full text |Cite
|
Sign up to set email alerts
|

<strong>Toward a comprehensive COI DNA barcode library for Swiss Stoneflies (Insecta: Plecoptera) with special emphasis on the genus <em>Leuctra</em></strong>

Abstract: The Swiss Barcode of Life initiative (SwissBOL) aims to inventory the genetic biodiversity in Switzerland using a short DNA sequence. DNA barcoding provides an additional tool for species identification that complements traditional morphological approaches. We report on the establishment of a DNA barcode library for Plecoptera, taxa that are of great importance as bioindicators of water quality and that often present difficulties in species-level identification for larvae and female specimens. Non-destructive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Compared to the usual distances between different Labiobaetis species in that region and because there is no morphological difference, this distance is surprising, but can be still considered as intraspecific. Ball et al (2005) also reported a case with 6% intraspecific distance in a mayfly in North America and intraspecific K2P distances of more than 3.5% are also not uncommon within Plecoptera (Gill et al 2015, Gattolliat et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the usual distances between different Labiobaetis species in that region and because there is no morphological difference, this distance is surprising, but can be still considered as intraspecific. Ball et al (2005) also reported a case with 6% intraspecific distance in a mayfly in North America and intraspecific K2P distances of more than 3.5% are also not uncommon within Plecoptera (Gill et al 2015, Gattolliat et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular study: DNA was extracted from specimens stored in the collection of the Museum of Zoology in Lausanne, using a non-destructive method allowing a posteriori morphological identification. 658 bp of the mitochondrial protein-coding gene cytochrome c oxydase subunit I (CO1) was amplified using the primers LCO1490 and HCO2198 (for details see Gattolliat et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…All specimens are listed in Table 1. Sequences of Leuctra hippopus Kempny, 1899 and Leuctra pseudorosinae Aubert, 1954 were added to the data matrix as outgroups, as these have the most similar mitochondrial haplotypes according to Gattolliat et al (2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations